DESIGN AV HÖJ- & SÄNKBART SOFFBORD : Utvecklingsarbete mot Tenzo AB - Holmström, Anders; Gaversjö, Pontus (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2018)
In a world that only spins faster and where information is available in abundance, the need to multi task has grown bigger than ever before. The need to eat or work from the sofa is growing, while the trends say that the coffee table should be low. This conflict of interest forces people to make a choice, following the trends or being able to easily multi task from the sofa. Or do they have to? The thesis work described in this report may provide a solution to the problem. The work consists of 10 credits and is carried out by two students as a final stage of the bachelor’s degree in Industrial Design Engineering at Luleå University of Technology. The work is carried out in collaboration with the furniture manufacturer Tenzo AB. Tenzo is a, privately owned, Swedish furniture manufacturer with a business idea aimed at trendy furniture in the international market, according to Tenzo (2018), 95% is exported to Europe and major retailers in France, Germany and Switzerland. The goal has been to develop a conceptual lift top coffee table. With a user-centered design process, the user was involved continuously throughout the work, during a workshop and in interviews with the goal of exploring the question ”What is important in a coffee table?”, in evaluative interviews and in Virtual Reality (VR) to test the concepts and ideas. The final concept embraces a more classical table shape than the lift top tables available on the market today, but is also developed with future trends in mind. The trends identified are colors with more hue than the bright pastels we see today, rounder and softer shapes than the boxynes observed among today’s lift top coffee tables, and that the light wood is replaced by darker woods. The color options presented give the table both the ability to melt into an environment or stick out and demand presence in the room.